1992
DOI: 10.1002/jmv.1890360104
|View full text |Cite
|
Sign up to set email alerts
|

Significance of serum IgM anti‐HBc in chronic hepatitis B virus infection

Abstract: Because of widely differing reports on the significance of IgM anti-HBc in chronic hepatitis B virus (HBV) infection, paired sera and liver biopsies from 49 patients with chronic HBV infection were analysed for serum IgM anti-HBc, HBsAg titre, HBeAg/anti-HBe, HBV DNA, serum aspartate transaminase, intrahepatic HBcAg expression, and liver histology. High levels of IgM anti-HBc, in the diagnostic range of acute hepatitis B (greater than 1.2), were detected in seven patients (14.3%) and a total of 34 patients (69… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 16 publications
(12 reference statements)
0
18
0
Order By: Relevance
“…The loss of HBeAg in chronic HBV carriers generally represents a late phase in the course of chronic HBV infection (89). Low levels of anti-HBc IgM are frequently detected in patients with chronic HBV infection, albeit without any diagnostic significance (244). Estimation of HBV DNA levels is one of the most useful markers in the management of chronic hepatitis B. Estimation of HBV DNA and ALT levels in serum, the presence of HBeAg, and the assessment of liver histology help in the evaluation and identification of patients requiring antiviral treatment for chronic hepatitis B (268).…”
Section: Diagnosismentioning
confidence: 99%
“…The loss of HBeAg in chronic HBV carriers generally represents a late phase in the course of chronic HBV infection (89). Low levels of anti-HBc IgM are frequently detected in patients with chronic HBV infection, albeit without any diagnostic significance (244). Estimation of HBV DNA levels is one of the most useful markers in the management of chronic hepatitis B. Estimation of HBV DNA and ALT levels in serum, the presence of HBeAg, and the assessment of liver histology help in the evaluation and identification of patients requiring antiviral treatment for chronic hepatitis B (268).…”
Section: Diagnosismentioning
confidence: 99%
“…In chronic infections, such as chronic hepatitis B (HB), it has been demonstrated that IgM antibodies to the nucleocapsid of HBV (anti-HBc) persist in circulation [Banninger et al, 1983;Chau et al, 1983;Cappel et al, 1981;Gerlich et al, 1980;Kiyosawa et al, 1986;Lemon et al, 1981;Roggendorf et al, 1981;Sjogren and Hoofnagle, 1985;Smith et al, 1992;Surrenti et al, 1986;Tedder and Wilson-Croome, 19811, and this persistence correlated with viral replication [Banninger et al, 1983;Kiyosawa et al, 1986;Sjogren and Hoofnagle, 1985;Roggendorf et al, 19811, the biological activity of chronic hepatitis B [Feinman et al, 19821 and a more aggressive state of the disease [Cappel et al, 19811. The IgM antibody has a similar prognostic value in chronic hepatitis delta virus (HDV) infection [Rizzetto, 1983;Smedile et al, 19821, where is has been found that the presence of IgM anti-HD correlated with underlying liver inflammation and was predictive of cirrhosis [Buti et al, 1987;Farci et al, 19861.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] However, IgM anti-HBc may become detectable during acute flare of chronic hepatitis B. 12,13 The index value of IgM anti-HBc would be a useful serologic marker to differentiate acute hepatitis B (AHB) from acute flare of chronic hepatitis B (CHB). 10,11,[14][15][16][17] Higher index values of IgM anti-HBc were found in AHB, while lower index values were detected in CHB.…”
Section: Introductionmentioning
confidence: 99%